Dynamic ultrasonic visualization of blood vessels and flows - NOWICKI, Andrzej; REID, John M. (Archives of Acoustics, 1982)
This paper describes a new method for dynamic real-time visualization of blood flows. This method uses a special signal processing system (SEC) which consists in cancellation of stationary echoes from the reflections of ultrasonic waves from soft tissues with continuous measurement of the phase of signals scattered in blood.The stationary echo cancellation system has been designed on the basis of the properties of periodic filters using quartz delay lines. A level of stationary echo cancellation above 55 dB was achieved, which, when using an original detector of the phase of signals scattered in blood, permits real-time observation of blood flow velocity profiles. This, in turn, permits the internal diameter of a vessel (the degree of constriction) to be evaluated in the site under investigation.